2000
DOI: 10.1002/clc.4960230813
|View full text |Cite
|
Sign up to set email alerts
|

Exercise conditioning and heart rate variability: Evidence of a threshold effect

Abstract: Background: A protective effect of exercise in preventing sudden cardiac death is supported by studies in healthy populations as well as in patients with cardiac disease. The mechanisms involved in this protective effect are unknown. Hypothesis: We hypothesized that exercise conditioning would beneficially alter autonomic nervous system tone, measured by heart rate variability. Methods: We prospectively studied 20 cardiac patients enrolled in a Phase 2 12-week cardiac rehabilitation program following a recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 26 publications
1
21
3
Order By: Relevance
“…Our findings agree with previous data reporting a 25% increase in short-term SDNN in patients undertaking 8 weeks of CR commencing 4 weeks after first uncomplicated MI [21] and from several studies using ambulatory ECG recordings [19,32] The data, however, differ from those of Duru et al [8] and Pardo et al [26] who found no such changes. RMSSD is predominantly mediated by vagal activity and over the course of CR there was a non-significant (P = 0.09) increase.…”
Section: J Time Domain Variablessupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings agree with previous data reporting a 25% increase in short-term SDNN in patients undertaking 8 weeks of CR commencing 4 weeks after first uncomplicated MI [21] and from several studies using ambulatory ECG recordings [19,32] The data, however, differ from those of Duru et al [8] and Pardo et al [26] who found no such changes. RMSSD is predominantly mediated by vagal activity and over the course of CR there was a non-significant (P = 0.09) increase.…”
Section: J Time Domain Variablessupporting
confidence: 84%
“…RMSSD is predominantly mediated by vagal activity and over the course of CR there was a non-significant (P = 0.09) increase. Previous studies [20,21] have shown very large (25-69%) changes in analogous measures (MSSD) whereas ambulatory data have shown no change [26,32] j Frequency domain measures…”
Section: J Time Domain Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation of sympathetic activity and increased vagal tone, effecting decreased vascular resistance, is a recognized adaptation to chronic endurance training (35). In contrast to these findings, LT-E 2 -deficient women demonstrate increased regional vascular resistance despite exposure to chronic aerobic exercise training.…”
Section: Discussioncontrasting
confidence: 48%
“…Spouse correlation, however, may also reflect assortative mating for exercise behavior, a variable known to be associated with SDNN index. 26 It is of note that the age-corrected sibling correlations in the Framingham Study (0.23 to 0.26) correspond very closely to our agecorrected sibling correlations, suggesting that, when the studies can be compared directly, they are actually very consistent.…”
Section: Discussionmentioning
confidence: 66%